2020
DOI: 10.12968/ijtr.2019.0064
|View full text |Cite
|
Sign up to set email alerts
|

Results of a UK-wide vignette study with occupational therapists to explore cognitive screening post stroke

Abstract: Background/Aims There is a paucity of evidence in the UK regarding cognitive screening performed by occupational therapists and whether, and how, cognitive impairments are identified and assessed. The aim of this study was to identify current occupational therapy practice for the assessment of cognitive problems in patients following stroke. Methods Occupational therapists were invited to complete an online vignette study. Participants were asked to: identify any presenting cognitive problems; decide whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This variation seemed to depend on the occupational therapists’ judgement of the patients’ cognitive problems and of their circumstances. These findings reflect results from an earlier phase of the COMPASS study (Geraghty et al., 2019), where occupational therapists were asked to comment on patient scenarios. These findings demonstrated inconsistencies in the identification of cognitive problems and also found a large number of cognitive assessments to screen patients were being suggested.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This variation seemed to depend on the occupational therapists’ judgement of the patients’ cognitive problems and of their circumstances. These findings reflect results from an earlier phase of the COMPASS study (Geraghty et al., 2019), where occupational therapists were asked to comment on patient scenarios. These findings demonstrated inconsistencies in the identification of cognitive problems and also found a large number of cognitive assessments to screen patients were being suggested.…”
Section: Discussionsupporting
confidence: 75%
“…All participants demonstrated sound working knowledge of community stroke rehabilitation. Sixteen of the participants had also taken part in an earlier phase of the COMPASS study (Geraghty et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four related studies (Geraghty et al, 2019; Koh et al, 2009; Korner-Bitensky et al, 2011; Pilegaard et al, 2014) focused on the assessment of individuals with mild cognitive impairment post stroke and participants were predominantly experienced OTs, with 5–10 years of stroke experience. These studies found that while OTs preferred using functional cognitive assessments, because they are client centred and meaningful to the patient (Koh et al, 2009), there was a wide variability in their content (Pilegaard et al, 2014).…”
mentioning
confidence: 99%